Samaki Salama – Promoting healthy child growth and sustainable fisheries in coastal Kenya: A study protocol - Blackmore, Ivy; Wamukota, Andrew; Kamau-Mbuthia, Elizabeth; Humphries, Austin; Lesorogol, Carolyn; Cohn, Rachel; Sarange, Catherine; Mbogholi, Francis; Obata, Clay; Cheupe, Christopher; Cheupe, Joaquim; Sherburne, Lisa; et al. (Frontiers in Public Health, 2022)
Background: One in five young children globally suffer the consequences of stunted growth and development and millions experience deficiencies in zinc, iron, iodine, vitamins A and B12, nutrients found bioavailable in fish foods. Small-scale fisheries have the potential to generate income and augment fish consumption while being environmentally sustainable if appropriately managed. However, those engaged in small-scale fisheries are often marginalized, poor, and malnourished. The Samaki Salama project seeks to better understand and address these challenges through a three-arm, longitudinal matched cluster study which evaluates the impact of an integrated nutrition social marketing and modified fishing trap intervention. Methods: There will be 400 small-scale fisher households enrolled from Kilifi County, Kenya and residing in communities matched on location (rural), livelihoods, and child nutritional status. The sample will include mothers and other caregivers, children 6-60 months, and fishers in the family. Applying a cluster design, the matched communities will be divided into three groups: (1) control (n=200); (2) multi-component nutrition social marketing intervention to fishers, mothers, and health workers (n=100); and (3) multi-component nutrition social marketing intervention plus modified fishing traps and training (n=100). Primary outcomes include child growth, fish food intakes, and fisheries yield of mature fish. Secondary outcomes are diet diversity, child diarrheal morbidity, and fisheries revenue. A process evaluation will be used to monitor and ensure fidelity of intervention delivery. Discussion: This study builds on a growing body of literature illustrating the effectiveness of nutrition focused social marketing campaigns to promote active engagement of participants, high compliance to the intervention, and sustained behavior change. The second intervention element of modified fishing traps that allow immature fish to escape enables participants to act on the messaging they receive and promotes sustainable fishing through increased harvest efficiency and reduced catch of immature fish. The integrated approach of the Samaki Salama intervention provides an example of how to leverage multiple disciplines to address key challenges to human and environmental health and illustrates a pathway for scaling study innovations to other small-scale fisheries systems.